Uma análise interpretativa dos conteúdos da matemática pura apresentados nos trabalhos de conclusão de curso na licenciatura em matemática da uft. - SILVA, Paulo Sergio Oliveira (Universidade Federal do Tocantins, 2023)
In this search we seek to understand the pure mathematics presented in the work of completion of course in degree in Mathematics from the UFT. The inquiry of this research is: what themes of Pure Mathematics are being addressed in the TCC's of course degree in Mathematics and what problems are being solved? Our goal is to show the themes of Pure Mathematics which is evidenced in surveys of academics of the course degree in Mathematics of UFT, Araguaína, and what problems they solve in parallel to these contents in their work of completion of the course. For this, we used the Phenomenology as a research methodology to analyze data, and as a phenomenological posture. We understand that many of the themes that were revealed in the survey are not in the menus of the disciplines of Pure Mathematics of the current curriculum of the course , according to the PPC (2012 ). So we realized that it is necessary to create spaces for studying the Pure Mathematics. The spaces to which we refer can be from inclusion of content that are being searched in the menus of the subjects, to the possibility of the inclusion of new disciplines in the current curriculum to meet this demand , or even the possibility of a project with objective a course of Bachelor of Mathematics at the UFT.